Reduction of body weight, liver steatosis and expression of stearoyl-CoA desaturase 1 by the isoflavone daidzein in diet-induced obesity. - Crespillo, Ana; Alonso, M; Vida, Margarita; Pavón, Francisco Javier; Serrano, A; Rivera-González, Patricia; Romero-Zerbo, Silvana Yanina; Fernández-Llebrez, Pedro; Martínez, A; Pérez-Valero, V; Bermúdez-Silva, Francisco Javier; Suárez-Pérez, Juan; et al. (Wiley, 2011)
Background and purpose. The lack of safe and effective approved drugs against obesity has raised a great interest on natural products that may serve as alternative therapies. From this perspective we have addressed the analysis of the effects of daidzein, one of the main soy isoflavones, on diet induced obesity in rats. Experimental approach. Rats made obese after exposure to a very (60%) high fat content diet were treated with Daidzein (50 mg/kg) for 14 days. The dose was selected on the basis of the acute effects of this isoflavone on a feeding test. After 14 days, animals were sacrificed and plasma, white and brown adipose tissues, muscle and liver studied for the levels and expression of metabolites, proteins and genes relevant for lipid metabolism. Key results. Acute daidzein dose-dependently reduced food intake. Chronic treatment reduced weight gain and reduced fat content in the liver. This was associated with high leptin levels and low adiponectin contents in plasma. While skeletal muscle was weakly affected by treatment, both adipose tissue and liver displayed marked changes induced by daidzein that affect transcription factors and lipogenic enzymes, specially stearoyl coenzyme A desaturase-1, a pivotal enzyme in obesity. Protein expression of the uncoupling protein 1, an important enzyme involved in thermogenesis, was increased in brown adipose tissue after daidzein treatment. Conclusions and implications. These results give support to the use of isoflavones in diet induced obesity, especially when hepatic steatosis is present, opening a new field of use for these natural products
Keywords: Obesidad - Tratamiento; Daidzein; Diet-induced obesity; Oxidative metabolism; SCD1; UCP1; PPAR; Cannabinoid receptor; Skeletal muscle; Liver; Adipose tissue